A new hybrid genetic algorithm-sarima-artificial neural network in forecasting Malaysian export amount of palm oil - Chai, Kah Chun (2021)
Malaysia is a significant export country of palm oil to all over the world. Therefore, forecasting of palm oil export is required to help in boosting the nation’s socioeconomic